Be proactive or inactive: The effects of systematic job riskiness on effort investment. (28th January 2020) - Yang, Fanzheng; Shi, Yujiao; Weng, Weiwei
Abstract : A company's success heavily relies on its employees' willingness to take initiative at the workplace. With three representative types of risky environments introduced and a series of incentive schemes implemented in the order that mimics the trial process of a company's search for an effective incentive design, we experimentally explore the interplay between systematic job riskiness and managerial practices in determining individuals' risky effort input. Our findings demonstrate that the effectiveness of typical motivational practices, including competitive schemes and the combined use of peer feedback, could vary across risky working environments systematically.